The Effect of Dietary Electrolyte Balance on Growth, Tibia Ash and Some Blood Serum Electrolytes in Young Pullets - Moghaddam, H. Nassiri; Janmohammadi, H.; Najafabadi, H. Jahanian (International Journal of Poultry Science, 2005)
This study was conducted to evaluate the effect of increasing dietary electrolyte balance [DEB; Na + K - Cl, miliequivalents (mEq) Kg-1 on growth performance, tibia ash and Ca, Na, K and Cl contents of blood serum in young pullets. A corn-soybean meal based mash diet containing 187 mEq Kg-1 (Na + K - Cl) was formulated to supply the nutrient requirements of young pullets. DEB of basal diet was increased as much as 43, 64 and 97 mEq Kg-1 by substitution of sodium bicarbonate, potassium bicarbonate or both of them in part of corn and four experimental diets containing 187, 230, 251 and 284 mEq Kg-1 (Na + K - Cl) were obtained. Young pullets (n=160) were used from 7 to 35 d of age, in a completely randomized design with four dietary treatments having four replicate cages (10 pullets) each to evaluate different levels of DEB. Weekly feed intake, body weight gain and feed conversion ratio were not significantly affected by dietary treatments. The same results were obtained in growth period of 7 to 35 days. Tibia ash and its calcium content varied between 46.5 to 48.9 and 34.4 to 37.9 percent, respectively and were not significantly affected by different levels of DEB. Among blood serum electrolytes, only K and Cl were significantly affected by DEB (P< 0.01). Diet containing 251 mEq Kg-1 (Na + K - Cl) had the lowest value of blood serum K concentration and concentration of blood serum Cl increased with increasing of DEB.